A history of Germany, 1918 - 2014 the divided nation - Fulbrook, Mary 1951- (Wiley-Blackwell, 2015)
"The fourth edition of A History of Germany, 1918-2014: A Divided Nation introduces students to the key themes of 20th century German history, tracing the dramatic social, cultural, and political tensions in Germany since 1918. Now thoroughly updated, the text includes new coverage of the Euro crisis and a review of Angela Merkel's Chancellorship. New edition of a well-known, classic survey by a leading scholar in the field, thoroughly updated for a new generation of readers. Provides an overview of the turbulent history of Germany from the end of the First World War through the Third Reich and beyond, examining the character and consequences of war and genocide. Treats German history from 1918 to 2014 from the perspectives of instability, division and reunification, covering East and West German history in equal depth. Offers important reflections on Angela Merkel's Chancellorship as it extends into a new term. Concise, substantive coverage of this period make it an ideal resource for undergraduate students"--
Previously published under the title: A history of Germany, 1918-2008
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Geschichte 1918-2014; HISTORY / Modern / 20th Century; Politik; Germany / Politics and government / 20th century; Germany / Politics and government / 21st century; Deutschland